Public Speaking Anxiety: Strategies For Overcoming the Fear of Speaking in Public - Islomova Sevinch Botirjon qizi (Academia One Publishing, 2023)
Public speaking anxiety is a common and often paralyzing fear that affects individuals in various personal and professional contexts. This article explores the roots of public speaking anxiety, its detrimental effects, and practical strategies for overcoming this fear. By examining psychological techniques, preparation methods, and real-world examples, this comprehensive guide aims to help individuals build confidence and become more effective and persuasive public speakers.
Keywords: Public speaking anxiety; fear of public speaking; presentation anxiety; confidence in public speaking